Differential Surgical Tactics in Complicated and Complex Forms of Liver Echinococcosis (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Purpose of the study. To improve the results of surgical treatment of liver echinococcosis and its complications by developing differential tactics with a priority use of minimally invasive technologies. Study materials. Depending on the type and number of operations and examinations performed, patients were divided into two groups. In the main group of 118 patients (2021-2023), surgical treatment using modern diagnostic methods and minimally invasive technologies was used. The comparison group included 106 patients who underwent traditional diagnostic methods and open surgical interventions. Study results. Surgical treatment of liver echinococcosis and its complications using minimally invasive technologies made it possible to significantly improve treatment results by reducing postoperative complications from 21.7% to 9.3%, eliminating deaths, and reducing recurrences from 14.8% to 5.4%.